Influence of Inorganic and Organic Fertilizers on Growth and Yield of Soybean - Mamia, A; Amin, AKMR; Roy, TS; Faruk, GM (Bangladesh Agronomy Journal, 2018)
The experiment was executed at the Agronomy researchfield of Sher-e-Bangla Agricultural University, Dhaka-1207, during the period from November, 2015 to March, 2016 to study the effects of fertilizer management of different combinations of inorganic and organic fertilizers on growth, yield attributes and yield of soybean (var. BARI Soybean 6). The treatment combinations wereT0= Control, T1= fertilization at recommended fertilizer dose (RFD - urea 50 kg ha-1, TSP 150 kg ha-1, MoP 100 kgha-1, gypsum 80 kg ha-1 and boron 500 kg ha-1), T2= Bio-fertilizer + 50% RFD, T3= Biofertilizer + 75% RFD, T4= Mixed fertilizer + 50% RFD, T5= Mixed fertilizer + 75% RFD, T6= Vermi-compost + 50% RFD, T7= Vermicompost + 75% RFD, T8= Poultry litter + 50% RFD and T9= Poultry litter + 75% RFD. Results indicated that application of fertilizer at recommended dose, vermi-compost + 75% RFD and poultry litter + 75% RFD produced higher grain yield 2053, 2073 and 2166 kg ha-1, respectively over control. It was also observed thatconsidering the sustainable yield and environment friendly,poultry litter + 75% RFD (T9) and vermi-compost + 75% RFD (T7) couldbe promising for soybean cultivation. Bangladesh Agron. J. 2018, 21(1): 77-81